Tindak Pidana Penganiayaan Terungkap Direncanakan Terlebih Dahulu Mengakibatkan Korban Luka-Luka (Studi Putusan PN Brebes Nomor: 57/ Pid.B /2020 / PN.BBs.).” - Adde Pramana Putra; Aprima Suar (Reformasi Hukum Trisakti, 2023)
Based on how these actions affect the victims, material criminal law is applied to acts of persecution. The elements of the persecution offense that were broken will determine how the victim of the crime is punished. The issue is whether the criminal act of persecution in the case of Brebes District Court Decision No: 57/Pid.B/2020/PN.BBs., satisfies the criminal elements of Article 351 paragraph (1) of the Criminal Code, and how the criminal act of persecution in the case of the Brebes District Court Decision is subject to material criminal law. The research approach makes use of a particular sort of study, namely normative legal research, which has an analytical descriptive research nature. and the type of data used is secondary data, analyzed qualitatively to then draw conclusions deductively. The results of the research, discussion and conclusion are that the abuse committed by the Defendant against the Victims and concluded from witness statements, the confessions of the accused and from the results of the Visum Et Repertum, fulfill the criminal elements of Article 351 paragraph (1) of the Criminal Code. However, the application of the material criminal law by the Panel of Judges at the Brebes District Court was inappropriate, because the legal facts revealed at trial showed that the sickle used by the Defendant had been prepared beforehand, so that the application of material punishment to the case was a criminal act of premeditated persecution under Article 353 of the Criminal Code.